2002
DOI: 10.4049/jimmunol.169.12.6691
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Dynamic Redistribution of Tetraspanin CD81 at the Central Zone of the Immune Synapse in Both T Lymphocytes and APC

Abstract: The tetraspanin CD81 has been involved in T-dependent B cell-mediated immune responses. However, the behavior of CD81 during immune synapse (IS) formation has not been elucidated. We determined herein that CD81 redistributed to the contact area of T cell-B cell and T cell-dendritic cell conjugates in an Ag-dependent manner. Confocal microscopy showed that CD81 colocalized with CD3 at the central supramolecular activation complex. Videomicroscopy studies with APC or T cells transiently expressing CD81-green flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 25 publications
5
104
0
Order By: Relevance
“…MHC-II molecules loaded with specific antigenic peptides appear to be enriched in TEMs (30,47), and it has been suggested that TEMs might increase the chance of successful presentation of a limited pool of MHC-II molecules loaded with specific peptides. This would be in agreement with the observation that tetraspanins are constituents of IS (34). SCIMP is also rapidly translocated to IS.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…MHC-II molecules loaded with specific antigenic peptides appear to be enriched in TEMs (30,47), and it has been suggested that TEMs might increase the chance of successful presentation of a limited pool of MHC-II molecules loaded with specific peptides. This would be in agreement with the observation that tetraspanins are constituents of IS (34). SCIMP is also rapidly translocated to IS.…”
Section: Discussionsupporting
confidence: 80%
“…Thus far, we have demonstrated that SCIMP is a part of MHC-II-containing TEMs. Some of the tetraspanins have been shown to partition to the IS between the APC and the T cell (34). To find out whether SCIMP may also localize to the IS, we used Ramos and Daudi B cell lines expressing SCIMP-GFP as APCs in a superantigen staphylococcal enterotoxin E (SEE)-based assay.…”
Section: Resultsmentioning
confidence: 99%
“…35,36 We have demonstrated that CD26 is costimulatory for CD3-induced signal transduction and targeting of CD26 to lipid rafts is necessary for signaling events through CD26. 16 We first investigated whether disruption of lipid rafts' integrity via cholesterol extraction with M␤CD would inhibit CD26-induced signal transduction.…”
Section: Lack Of Cd26 Recruitment Into Lipid Rafts Following Antibodymentioning
confidence: 99%
“…Tetraspanins play a role in membrane fusion, cell migration, and in signal transduction (29)(30)(31)(32). The role of CD81 as a costimulatory molecule is of special interest because it has been shown to localize at the site of interaction between B cells and T cells in a central supermolecular cluster (33).…”
Section: A Ctivation Of Naïve T Cells Requires Two Independent Signalsmentioning
confidence: 99%